Plant genome engineering from lab to field—a Keystone Symposia report. Issue 1 (25th August 2021) - Cable, Jennifer; Ronald, Pamela C.; Voytas, Daniel; Zhang, Feng; Levy, Avraham A.; Takatsuka, Ayumu; Arimura, Shin‐ichi; Jacobsen, Steven E.; Toki, Seiichi; Toda, Erika; Gao, Caixia; Zhu, Jian‐Kang; et al.
Abstract: Facing the challenges of the world's food sources posed by a growing global population and a warming climate will require improvements in plant breeding and technology. Enhancing crop resiliency and yield via genome engineering will undoubtedly be a key part of the solution. The advent of new tools, such as CRIPSR/Cas, has ushered in significant advances in plant genome engineering. However, several serious challenges remain in achieving this goal. Among them are efficient transformation and plant regeneration for most crop species, low frequency of some editing applications, and high attrition rates. On March 8 and 9, 2021, experts in plant genome engineering and breeding from academia and industry met virtually for the Keystone eSymposium "Plant Genome Engineering: From Lab to Field" to discuss advances in genome editing tools, plant transformation, plant breeding, and crop trait development, all vital for transferring the benefits of novel technologies to the field. Abstract : Facing the challenges of the world's food sources posed by a growing global population and a warming climate will require improvements in plant breeding and technology. The advent of new tools, such as CRIPSR/Cas, has ushered in significant advances in plant genome engineering. However, several serious challenges remain in achieving this goal. Among them are efficient transformation and plant regeneration for most crop species, low frequency of some editing applications, and high attrition rates. On Demand content : https://keysym.us/EK25NYAS